Control and Guidance of an Underwater Robot via Fuzzy Control Method - Mehdi Ghanavati; Afshin Ghanbarzadeh (International Journal of Advanced Design and Manufacturing Technology, 2010)
In this project guidance and control of underwater robot, including three engines and propeller attached to it, by Fuzzy control has been investigated. Fuzzy control is done based on human experience and requiered laws. The robot can also be controlled and guided by the user. This robot may be used in sea or swimming pool environment for finding goal point and locate in desired direction. In addition, this robot is able to follow a definite path and to do searching operation in that path. This robot is also able to overtake barriers on the surface or under the surface and forward toward target and path the barriers using fuzzy rules. In other words, while facing any barriers using fuzzy rules. In other words, while facing any barrier, robot decides necessary decision in such a way not to collide with it and path it. For simulation of the required system, webots' software which is strong software for mobile robot simulation and Maple's material software is used. This robot is capable to distance any obstacle in 3D and move towards the goal. Obstacle avoidance is done by fuzzy rules. Means when face any obstacle, the underwater robot decide for not collision and passes it. For the simulation system, Webots that is strong software for mobile robot simulation and mathematical software Maple is used.